2022
DOI: 10.33200/ijcer.1026655
|View full text |Cite
|
Sign up to set email alerts
|

Examining Non-cognitive Factors Predicting Reading Achievement in Turkey: Evidence from PISA 2018

Abstract: The purpose of the study was to investigate how student and teacher-related non-cognitive variables were important factors on the reading performances of Turkish students in PISA 2018. The results of the HLM analysis revealed that economic, social and cultural status (ESCS) as backround variable was considered an effective predictor of student and school reading achievement. Meta-cognitive stratejies were the most influential variables among the students’ non-cognitive variables. Besides, most of the teacher-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…In terms of performance level, students who report to have been "almost never" helped or "sometimes" helped when they have difficulties are at the bottom. Karaman (2022) found out that the adaptation of instruction showed a positively significant relationship with reading literacy in Türkiye. Adapting the course requires expert knowledge.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…In terms of performance level, students who report to have been "almost never" helped or "sometimes" helped when they have difficulties are at the bottom. Karaman (2022) found out that the adaptation of instruction showed a positively significant relationship with reading literacy in Türkiye. Adapting the course requires expert knowledge.…”
Section: Discussionmentioning
confidence: 93%
“…Meşe-Soytürk (2020) investigated teacher support including emotional support and found out that the highest impact on the reading skills of 15-year-old students studying in Türkiye was positively related to the classroom discipline, family support, reading competence perceptions, feeling of a sense of belonging to the school, respectively, and negatively related to teacher support. Karaman (2022) examined the relationship between teacher behavior and reading performance in PISA 2018 and found that the students who felt supported by their teachers showed higher performance in reading literacy. The feedback perception of the students in the Turkish/Turkish Language and Literature course was also seen to be related to the average scores of the general reading scale.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The outstanding performance of the top performing regions has always attracted researchers to study the factors underpinning their academic success (e.g., Lau & Ho, 2015;Qian & Lau, 2022). Instructional practice is among one of the key factors contributing to high levels of reading performance (Karaman, 2022;Nurmi et al, 2013;OECD, 2019a). While a plethora of research has investigated the associations between instructional practices and reading performance, relatively little attention is given to the role of cultural context in shaping this relationship (Haw & King, 2022).…”
Section: Introductionmentioning
confidence: 99%